Perbaikan Instalasi Listrik dan Sistem Penerangan Untuk Menunjang Desa Wisata Pulau Mubud Darat - Adlian Jefiza; Ahmad Riyad Firdaus; Sumantri Kurniawan Risandriya; Muhammad Arifin; Widya Rika Puspita; Mustanir Mustanir; Riki Ria; Indra Daulay; Ira Zamzami; Ghozalli Mashan; Dwi Imam Mulyono (Pusat P2M Politeknik Negeri Batam, 2022)
One of the tourist attractions in the city of Batam is the tourist village of Pulau Mubud Darat. Mubud Darat Island is separated from Batam Island. On the island of Mubud Darat has a beautiful beach with white sand on the shoreline. However, on the island of Mubud Darat, there is no PLN electricity. The electricity that flows on Mubud Darat Island is still sourced from generators with diesel fuel. Electrical installations on the island of Mubud Darat are also not safe for visitors. This requires large costs for tourism operations both for operations and installation repairs. In addition, to increase the interest of visitors on Mubud Darat island, a good photo spot icon is needed which will later become an icon for Mubud Darat Island. Therefore, lighting is needed from solar panels, as well as repairs to electrical installations on Mubud Darat island. In addition, to create a tourist icon on Mubud Darat Island, a photo spot for the sky door is given which is added with LED strip lights.